2014
DOI: 10.1891/1521-0987.15.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Plans of Care to Improve Outcomes Among Children and Adults With Chronic Illness: A Systematic Review

Abstract: Current evidence supporting an association between IPC use and improved outcomes, particularly among children, is sparse. Well-designed evaluations of clearly described IPCs are needed to examine who should be involved in their development, what they should include, and how often they should be updated to improve outcomes of care for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
(91 reference statements)
1
24
0
Order By: Relevance
“…There is room for improvement since care planning discussions were noted by patients as reactive, rather than anticipatory and limited by time constraints [18]. The current literature is inconclusive on what components need to be included in a care plan to affect clinical outcomes in a positive manner [6]. One study on care plans included an element of goal setting with the patient and detailed information about lifestyle behaviors where self-management resulted in improved clinical core values of patients [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is room for improvement since care planning discussions were noted by patients as reactive, rather than anticipatory and limited by time constraints [18]. The current literature is inconclusive on what components need to be included in a care plan to affect clinical outcomes in a positive manner [6]. One study on care plans included an element of goal setting with the patient and detailed information about lifestyle behaviors where self-management resulted in improved clinical core values of patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Various academic bodies, including the American Academy of Family Physicians, endorse the use of an individualized care plan as a key element of the patient-centered medical home [6]. Studies have shown improvement in clinical outcomes secondary to the use of care plans [710].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While comprehensive biopsychosocial assessment is beyond the scope of this position paper and detailed elsewhere (Turk & Melzack, ), several aspects most relevant to exercise prescription are discussed. The initial assessment provides an opportunity to lay the foundation for a positive clinician–patient therapeutic alliance, which refers to a sense of collaboration, understanding and support between the clinician and the patient and is a key factor in determining rehabilitation outcomes (Ferreira et al, ; Lion, Mangione‐Smith, & Britto, ). Patient‐centred communication engages the patient and strengthens the therapeutic alliance (Ferreira et al, ; Lion et al, ) and should commence in the initial assessment and be ongoing throughout treatment.…”
Section: Applying a Biopsychosocial Approach To Exercise Treatmentmentioning
confidence: 99%